Sinkronisasi Peraturan Daerah Bernuansa Syariah Dengan Konstitusi Dan Undang Undang Nasional - Ade Maulana; Amalia Maryam Nur Rohmah; Amellia Azzahra; Elyza Dwi Kartika; Deden Najmudin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Synchronizing Sharia-based regional regulations with the constitution and national laws in the context of the Indonesian rule of law. The emergence of Sharia-based regional regulations after regional autonomy reflects the moral and religious aspirations of the Muslim community, but also poses challenges to the principles of pluralism, human rights, and constitutional supremacy. Through a juridical-normative approach and conceptual analysis, this study examines how the values of Maqasid al-Syariah can be integrated into the formation of regional regulations to maintain justice and inclusiveness. The results show that the application of Sharia values in public policy is acceptable only as long as it does not conflict with Pancasila, the 1945 Constitution, and the principle of equality of citizens. The integration of Maqasid al-Syariah serves as a normative bridge between Islamic law and national law, making Sharia-based regional regulations not merely religious symbols, but instruments for realizing public welfare, social justice, and order.